Predictors of health care workers' support for discriminatory treatment and care of people who inject drugs. Issue 4 (21st April 2019) - Brener, Loren; Cama, Elena; Broady, Timothy; Hopwood, Max; de Wit, John; Treloar, Carla
ABSTRACT: Complex lifestyle issues associated with injecting drug use may make it difficult to provide care to people who inject drugs (PWID). Negative attitudes towards PWID can undermine the provision of good quality care, hence, it is important to explore the impact of health workers' attitudes in the delivery of care to PWID. An online survey was administered to 336 health workers assessing contact with and attitudes towards PWID, concerns about these clients as well as whether health workers feel stigmatised by working with PWID. Health workers were also asked whether they supported the discriminatory behaviour of a colleague in a series of hypothetical scenarios about working with PWID. In correlational analyses, negative attitudes towards PWID, greater concerns about the behaviour of PWID, not feeling stigmatised by colleagues and seeing fewer clients who inject were associated with greater support for discriminatory actions in the hypothetical scenarios. Multiple regression analysis results showed that only attitudes towards PWID and concerns about the behaviour of injecting clients remain independent predictors of participant support for the hypothetical scenarios. This research highlights the role of attitudes toward PWID in understanding health workers' decisions, practices and potential behaviour.